A qualitative examination of affect and ideology within mass media interventions to increase HIV testing with gay men garnered from a systematic review. Issue 1 (31st July 2020) - Langdridge, Darren; Flowers, Paul; Riddell, Julie; Boydell, Nicola; Teal, Gemma; Coia, Nicky; McDaid, Lisa
Abstract : Objectives: Increasing appropriate HIV testing among men who have sex with men (MSM) is crucial to HIV prevention. Mass media interventions are effective in promoting testing, but to date, there has been little examination of their active content. Design: We conducted a qualitative analysis of intervention materials ( n  = 69) derived from a systematic review of mass media interventions designed to improve testing with MSM. Methods: Visual data were analysed for their affective and ideological content using a novel method drawing on concepts from semiotics (i.e., broadly speaking, the analysis of signs). Results: Whilst affect was not explicitly theorized or examined in any of the studies, there are clearly identifiable affective elements implicitly at play in these interventions. Four thematic categories of affect/ideology were identified including (1) sexual desire and the 'pornographication' of the gay/bisexual male subject; (2) narratives of romance and love; (3) fear, threat, and regret; and (4) 'flattened' affect. Conclusions: This is the first study to examine and detail the affective and ideological aspects of intervention content in this field. Using analytic techniques such as those reported here, in addition to approaches that focus on the manner in which intervention content address more proximal determinants of behaviour, can provide a rich and potentially more useful evidence base to assist with future interventions.